Pregnancy Risk Screening and Counseling for Women Veterans: Piloting the One Key Question in the Veterans Healthcare Administration. Issue 3 (March 2021) - Gawron, Lori M.; Simonsen, Sara; Millar, Morgan M.; Lewis-Caporal, Jessica; Patel, Shardool; Simmons, Rebecca G.
Abstract : Objectives: Women veterans have a high prevalence of comorbidities that increase the risk of adverse pregnancy outcomes. Screening for pregnancy desires in primary care provider (PCP) visits offers an opportunity to optimize preconception health. This pilot quality improvement initiative sought to assess Veterans Healthcare Administration provider preferences on One Key Question (OKQ) implementation, identification of veterans' reproductive needs, and the effect of training on documentation in a women's primary care clinic in Salt Lake City, Utah. Methods: We hosted OKQ training sessions for providers and staff, audio recorded group discussions on implementation barriers, and explored themes. Women veterans presenting for a PCP visit in July 2018 self-completed a paper OKQ screening tool. We calculated summary statistics on responses. We conducted a pre-post analysis, with respect to training sessions, to measure for changes in family planning documentation during PCP visits. Results: Nineteen providers and staff completed the training. They acknowledged the importance, but believed that the screening tool should be completed by veterans and not be provider prompted. Forty-two women veterans completed the screening tool: 21% desired pregnancy in the next year and 26% desired contraceptive information. Chart reviews found a nonsignificant increase in current contraceptive method documentation between periods (20% vs 37%; P = 0.08), a decline in documentation of reproductive goals (22% vs 3%; P = 0.02), and no significant change in counseling. Conclusions: Veterans identify reproductive needs via the OKQ screening tool, but provider documentation did not reflect changes in care following training. Further study is necessary to develop an optimal, patient-centered tool and implementation plan to support women veterans in their reproductive goals.